Feasibility and acceptability of an in-home digital device health and activity assessment platform in a diverse South Texas cohort: a pilot study - Mathews, Julia J.; Mulavelil, Rachel; Rodrigues, Nathaniel; Kautz, Tiffany F.; Cosgrove, Kevin; Wang, Chen-Pin; MacCarthy, Daniel; Fernandez, Roman A.; Gothard, Sarah; Sharma, Nicole; Serranorubio, Luis; Young, Vanessa M.; et al. (Frontiers in Digital Health, 2025)
IntroductionHealth tracking technologies hold promise as a tool for early detection of cognitive and functional decline.MethodsThis pilot study of 5 households [N = 7 residents, mean age: 74 (5), 71% Hispanic, 14% Black] used the Oregon Center for Aging & Technology (ORCATECH) platform to evaluate the technology and acceptance of the technology over a one-year interval in South Texas. Cognitive assessments and other surveys were administered at baseline and end-of-study visits.ResultsParticipants felt comfortable with the technology in their homes (86% Very Satisfactory or Satisfactory) and did not express privacy concerns (100% Very Satisfactory or Satisfactory).ConclusionHealth, cognition, and activity measures did not significantly change from baseline to end-of-study. Depression scores significantly improved (p = 0.034). The ORCATECH platform was an acceptable method of analyzing health and activity in a small, but diverse older population.